Cilia protein IFT88 regulates extracellular protease activity by optimizing LRP‐1–mediated endocytosis. Issue 12 (19th June 2018) - Coveney, Clarissa R.; Collins, Isabella; Fie, Megan Mc; Chanalaris, Anastasios; Yamamoto, Kazuhiro; Wann, Angus K. T.
ABSTRACT: Matrix protease activity is fundamental to developmental tissue patterning and remains influential in adult homeostasis. In cartilage, the principal matrix proteoglycan is aggrecan, the protease‐mediated catabolism of which defines arthritis; however, the pathophysiologic mechanisms that drive aberrant aggrecanolytic activity remain unclear. Human ciliopathies exhibit altered matrix, which has been proposed to be the result of dysregulated hedgehog signaling that is tuned within the primary cilium. Here, we report that disruption of intraflagellar transport protein 88 (IFT88), a core ciliary trafficking protein, increases chondrocyte aggrecanase activity in vitro.We find that the receptor for protease endocytosis in chondrocytes, LDL receptor‐related protein 1 (LRP‐1), is unevenly distributed over the cell membrane, often concentrated at the site of cilia assembly. Hypomorphic mutation of IFT88 disturbs this apparent hot spot for protease uptake, increases receptor shedding, and results in a reduced rate of protease clearance from the extracellular space. We propose that IFT88 and/or the cilium regulates the extracellular remodeling of matrix—independently of Hedgehog regulation—by enabling rapid LRP‐1–mediated endocytosis of proteases, potentially by supporting the creation of a ciliary pocket. This result highlights new roles for the cilium's machinery in matrix turnover and LRP‐1 function, with potential relevance in a range of diseases.—Coveney, C. R., Collins, I., Mc Fie, M., Chanalaris, A., Yamamoto, K., Wann, A. K. T. Cilia protein IFT88 regulates extracellular protease activity by optimizing LRP‐1–mediated endocytosis. FASEB J. 32, 6771–6782 (2018). www.fasebj.org